Implementing LiDAR-based SLAM algorithms for enhanced mapping and localization in physical robots - Ang, Ken Huat (Nanyang Technological University, 2024)
This study investigates SLAM techniques to overcome challenges in feature scarcity, computational load, and motion-induced distortions for autonomous mobile robots. Three SLAM algorithms are tested for LiDAR-inertial odometry, with FAST-LIO emerging as the recommended choice. Leveraging Livox MID-360 LiDAR, the study aims to enhance localization and situational awareness, expanding the practical applications of autonomous robots and UAVs.